(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Stunting is when a child fails to reach a height suitable for his age. The main cause is poor nutrition in pregnant mothers, babies, and infants. Stunting is one form of malnutrition, but it’s more accurately described as malnourishment. The use of caterpillars in the processing of MPASI and Supplements is one of the stunting prevention strategies. The purpose of this activity is to provide education about the fall of stunting. The method of implementation of this community service activity is through sliding. The samples used in this survey of stunting mothers and nutrition mothers were less than 25 people with children aged 6-60 months. The results of this examination showed that there was an increase in knowledge, attitude about stunting prevention with an abon belut with an average pre-test knowledge score of 76% and post-test 96%. This showed an improvement in knowledge and attitude of the young mother to be about 20%